2000
DOI: 10.1046/j.1524-4725.2000.99286.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Electrodessication with CO2 Laser for the Treatment of Actinic Cheilitis

Abstract: Although the healing time is longer with electrodessication, this modality represents an inexpensive practical ablative treatment method for actinic cheilitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 7 publications
(5 reference statements)
0
48
0
Order By: Relevance
“…compares the efficacy of electrodesiccation with CO 2 laser ablation for the treatment of AC. They reported that patients tolerated electrosurgery well and had no immediate discomfort; however, a burning pain did occur in the majority of patients shortly after the procedure 47 . The study indicated that on average, areas of AC treated with electrodesiccation took 8 days longer to heal compared with areas treated with CO 2 laser; this is probably resulting from collateral thermal damage 47 .…”
Section: Resultsmentioning
confidence: 99%
“…compares the efficacy of electrodesiccation with CO 2 laser ablation for the treatment of AC. They reported that patients tolerated electrosurgery well and had no immediate discomfort; however, a burning pain did occur in the majority of patients shortly after the procedure 47 . The study indicated that on average, areas of AC treated with electrodesiccation took 8 days longer to heal compared with areas treated with CO 2 laser; this is probably resulting from collateral thermal damage 47 .…”
Section: Resultsmentioning
confidence: 99%
“…As the three treated lesions received the same post procedural care, the significantly higher incidence of edema and tenderness in the lesions treated by electrodessication may be attributed to the extended zone of thermal damage commonly observed after the procedure [14]. As the three treated lesions received the same post procedural care, the significantly higher incidence of edema and tenderness in the lesions treated by electrodessication may be attributed to the extended zone of thermal damage commonly observed after the procedure [14].…”
Section: Discussionmentioning
confidence: 90%
“…It is simple, inexpensive, and readily available relative to other therapies, such as the CO 2 laser. 91 There seems to be no significant difference in the clinical results achieved with electrodessication when compared to CO 2 ablation. 91 Vermilionectomy involves the excision of all or part of the vermilion and closure of the labial mucosa to the skin of the outer lip.…”
Section: Surgical and Ablative Approachesmentioning
confidence: 91%
“…91 There seems to be no significant difference in the clinical results achieved with electrodessication when compared to CO 2 ablation. 91 Vermilionectomy involves the excision of all or part of the vermilion and closure of the labial mucosa to the skin of the outer lip. It is an extreme but excellent treatment option and is recommended for SC with severe dysplasia and SCC.…”
Section: Surgical and Ablative Approachesmentioning
confidence: 91%